A breakline-preserving ground interpolation method for MLS data. Issue 12 (2nd December 2019) - Xia, Shaobo; Chen, Dong; Wang, Ruisheng
ABSTRACT: Modelling accurate ground surfaces in urban areas is important for surveying and mapping. Breaklines along roads are critical for both digital elevation models and high precision maps. This article presents a new breakline-preserving ground interpolation method for point clouds acquired by mobile laser scanning (MLS). The proposed method needs only point coordinates as input. It first initializes unknown regions by the nearest neighbouring interpolation then matched patches in known regions are found along edges. Next, Poisson interpolation is utilized to improve the elevation accuracy. An edge-guided patch regularization method is applied before patch blending to remove noise and improve gradient accuracy. The proposed method was tested on two datasets acquired by different MLS systems. This paper quantitatively evaluates the proposed method as well as the existing solution in two samples of complete points. These results demonstrate that the proposed method outperforms the existing method in terms of visual coherence and mean absolute differences. Moreover, the edge information which is self-contained in point clouds has been proven useful in ground interpolation.